Length–weight relationships of six freshwater fish species from the middle section of the Yangtze River basin, China. (4th April 2022) - Dong, Fang; Yang, Haile; Zhou, Xianjun; Wan, Chaoyang; Xu, Lanxin; Zhang, Hui; Wei, Qiwei
Abstract: Six freshwater fish species belonging to two families were sourced from the middle section of the Yangtze River to analyze their length–weight relationships (LWRs). Fish specimens were collected seasonally using triple gillnet (30–50 m long, 2–4 m high, and mesh size, 2–3 cm) between September 2020 and August 2021. For each fresh specimen total length (TL) and weight were measured to the nearest 1.0 mm and 0.1 g. All LWR parameters of the six species were statistically significant ( p < .001). New maximum TL measures for four of the six fish species are recorded, and the LWRs of Ancherythroculter nigrocauda, Megalobrama mantschuricus, and Culter oxycephaloides are published herein for the first time. These results will contribute to fishery research, management, and conservation of the Yangtze River ecosystem.